Measurement-based ray-tracing models calibration of the permittivity and conductivity in indoor environments (2018)
In this paper, we show the results of a ray launching tool for channel estimation in indoor scenario and compare it with measurements in a DVB-T system, using a Vector Network Analyzer used to obtain the Root Mean Square Delay Spread (RMS-DS), obtained from S12 parameter. We use a 10mW transmitter and make measurements in 39 different points in the scenario. Also we show the empirical adjustments made in the constitutive parameters, in order to improve the Delay Spread results. We show that this kind of ray based tools are very sensitive to the number of interactions considered in the model and also to the values of the constitutive parameters of the different elements in the scenario. For the low frequencies used for this work, we found also that some external elements can influence the results and must be considered for indoor simulations.